Relativity : the Special & the General Theory - Einstein, Albert, 1879-1955 (Princeton University Press, 2019)
A handsome annotated edition of Einstein's celebrated book on relativityAfter completing the final version of his general theory of relativity in November 1915, Albert Einstein wrote Relativity. Intended for a popular audience, the book remains one of the most lucid explanations of the special and general theories ever written. This edition of Einstein's celebrated book features an authoritative English translation of the text along with commentaries by Hanoch Gutfreund and Jürgen Renn that examine the evolution of Einstein's thinking and cast his ideas in a modern context. Providing invaluable insight into one of the greatest scientific minds of all time, the book also includes a unique survey of the introductions from past editions, covers from selected early editions, a letter from Walther Rathenau to Einstein discussing the book, and a revealing sample from Einstein's original handwritten manuscript.